Tandem Organic Solar Cells: Nonfullerene Tandem Organic Solar Cells with High Open‐Circuit Voltage of 1.97 V (Adv. Mater. 44/2016). Issue 44 (17th November 2016) - Liu, Wenqing; Li, Shuixing; Huang, Jiang; Yang, Shida; Chen, Jiehuan; Zuo, Lijian; Shi, Minmin; Zhan, Xiaowei; Li, Chang‐Zhi; Chen, Hongzheng
Abstract : C.‐Z. Li, H. Chen and co‐workers present, on page 9729, for the first time, efficient non‐fullerene tandem organic solar cells (OSCs) by utilizing all non‐fullerene acceptor‐based bulk heterojunctions as sub‐cells. A high power conversion efficiency of 8.48% is achieved with an ultra‐high open‐circuit voltage of 1.97 V, which is the highest voltage value reported to date feasible for water splitting among the efficient tandem OSCs.